KUALITAS HASIL PERAWATAN AKHIR LENGKAP KERETA API DI UPT BALAIYASA MANGGARAI - Masjraul Hidayat; Dewi Indah Sari; Endang Sugiharti (Institut Transportasi dan Logistik Trisakti, 2017)
The objective of this study is to find out whether the maintenance process at UPT Balaiyasa Manggarai is controlled or not. UPT (Integrated Service Unit) Balaiyasa Manggarai is the only railway locomotive workshop that conducts facilities service operating in Java Island. Balaiyasa Manggarai gives 3-months guarantee, usually termed as the Balaiyasa Warranty Period (masa Tanggungan Balaiyasa) commencing from the train exit date from the balaiyasa. The research problem aroused in this study is there are still some trains that have to be returned to the maintenance because of failures during the warranty period. At the same time, Balaiyasa Manggarai ensures there should be a minimum or near-zero failures. The research method applied in this study was quantitative descriptive evaluation by using Quality Control Tools analysis technique and FMEA. Based on the Annual Railway Report in 2015-2016, there have been 33 failures during warranty periods from the total production of 416 trains. The result of U-Chart analysis shows that the maintenance process is still within the control limit because there are no points coming out of the UCL and LCL. The Pareto Chart shows that there is 1 failure which should be eliminated from the 4 failures to increase the quality of the trains.